The Freedom-based Critique of Well-Being's Exclusive Moral Claim. Issue 4 (2nd October 2021) - Fox, Joshua Isaac
ABSTRACT: Amartya Sen has suggested that the moral significance of freedom undermines the view that well-being alone possesses fundamental moral worth. Sen's efforts to establish this claim, however, seem to fall short: he attempts to establish freedom's independent moral significance by pointing to the value of autonomy, but explains the value of autonomy in terms of its role as an element of well-being. Nonetheless, I take it that Sen is very much on the right track: well-being is not the only fundamental moral value, and an examination of freedom's moral significance really will bring this out. I thus offer my own version of the freedom-based critique of well-being's exclusive moral claim, focusing not on autonomy but what Sen has called "well-being freedom." The value of this variety of freedom derives, I will suggest, not from the value of well-being itself but the value of well-being potential. Well-being freedom matters not only because promoting it is a way of promoting human well-being, but also because respecting it is a way of respecting the dignity of human nature. The freedom-based critique of well-being's moral uniqueness succeeds even if Sen's particular version of it does not.